A comparison of two group treatment methods of adolescent shyness - Somer, Zeynep. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1983., 1983)
The purpose of this study was to test the effectiveness of different group treatment procedures in reducing adolescent shyness. Subjects, ages between 15-16, were randomly assigned to one of the four groups, Cognitive Behavior Modification, Social Skills Training, Attention Control and Control. Treatment procedures in the three groups lasted for seven sessions, one forty minutes session per week. The distributiot by sex was equal in each group. In the Cognitive Behavior Modification procedure, half of each session was deVoted to the discussion of self-evaluations and worries of the subjects. The basic goal was to modify their maladaptive cognitions toward a more rational assessment of their situatinn. The remaining half of each session was devoted to a modified version of systematic desensitization. The Social Skills Training procedure consisted of training in basic skills of interpersonal behavior through the techniques of modeling, coaching, role-playing, homework and feedback.To investigate the effect of a group experience on the reduction of shyness, an Attention Control Group was formed and the topic of this group experience was irrelevant to the issue of shyness. It was hypothesized that, shyness, as indicated in the self-report measures used, and in the ratings of significant others (teachers and peers) would decrease as the result of treatment. A greater reduction was expected to be observed in the Social Skills Trainig Group compared to the Cognitive Behavior Modification Group. The results indicated that different treatment procedures did not create any significant decrease. Thus, the hypotheses were not supported. The nonsignificant findings were explained by the methodological limitations of the present study.
Keywords: Bashfulness in adolescence.; Interpersonal relations in adolescence.